A critical study on the implementation of hudud law in curbing sexual offences in Malaysia / Mohd Farid Zuhri Ismail...[et al.] - Ismail, Mohd Farid Zuhri; Abdul Wahid, Muhammad Abbad; Hamsar, Muhammad Khairi Aizuddin; Nor Ikhsan, Nor Ikhwan (Faculty of Law, 2012)
This project paper discusses about the issues and challenges in implementing Hudud law in Malaysia specifically on curbing sexual offences. The project paper outlines our research proposal which consists of basic layouts in conduct of our research. This project paper also comprises the explanation of Hudud law pertaining sexual offences and the problems of its enforcement in Malaysia. Furthermore this project paper also explains the legal issue in implementing Hudud law in Malaysia and compares with Hudud law applicable in Saudi Arabia. Besides, this project paper focuses on research finding based on knowledge of several parties in this topic and they had been interviewed to analyze on this matter which comprises of separate opinions and comments generated by legal and Hudud expertises. Last but not least, this project paper discusses on the recommendation on implementing Hudud law into our Malaysian legal system.